Effect of Ascorbic Acid and Alpha-tocopherol Supplementation on Plasma Corticosterone and Production Performance of Commercial Broilers - Sheikh, Amir Amin (Indian Journal of Animal Nutrition, 2021)
The present investigation studies the effect of ascorbic acid (AA) and alpha-tocopherol supplementation on plasma corticosterone and production performance of broilers. 84 day-old broiler birds were randomly assigned into seven groups of 12 each, namely G1, G2,G3,G4,G5,G6 and G7 maintained at 26Â±1.0Â°C. G1 group was taken as control, whereas G2, G3 and G4 groups were fed 100 mg/kg feed, 200 mg/kg and 300 mg/kg of ascorbic acid respectively with basal diet. Similarly, basal diet was supplemented with 100, 200 and 300 mg/kg of alpha-tocopherol in groups G5, G6 and G7, respectively. Weekly record of feed intake was made for six weeks. Body weight, and feed efficiency ratio was recorded at 1st, 3rd and 6th week. Lower (P